One-dimensional multichannel g-C3N4.7 nanostructure realizing an efficient photocatalytic hydrogen evolution reaction and its theoretical investigations - Antil, Bindu; Kumar, Lakshya; Ranjan, Ravi; Shenoy, Sulakshana; Tarafder, Kartick; Gopinath, Chinnakonda S.; Deka, Sasanka (ACS Applied Energy Materials, 2021)
The emerging metal-free carbon nitride (C3N4) offers prominent possibilities for realizing the highly effective hydrogen evolution reaction (HER). However, its poor surface conductivity and insufficient catalytic sites hinder the HER performance. Herein, a one-dimensional vermicular rope-like graphitic carbon nitride nanostructure is demonstrated that consists of multichannel tubular pores and high nitrogen content, which is fabricated through a cost-effective approach having the final stoichiometry g-C3N4.7 for HER application. The present g-C3N4.7 is unique owing to the presence of abundant channels for the diffusion process, modulated surface chemistry with rich- electroactive sites from N-electron lone pairs, greatly reduced recombination rate of photoexcited exciton pairs, and a high donor concentration (4.26 x 10(17) cm(3)). The catalyst offers a visible-light-driven photocatalytic H-2 evolution rate as high as 4910 mu mol h(-1)g(-1) with an apparent quantum yield of 14.07% at band gap absorption (2.59 eV, 479 nm) under 7.68 mW cm(-2) illumination. The number of hydrogen gas molecules produced is 1.307 x 10(15) s(-1) cm(-2), which remained constant for a minimum of 18 h of repeated cycling in the HER without any degradation of the catalyst. In density functional theory calculations, a significant change in the band offset is observed due to N doping into the system in favor of electron catalysis. The theoretical band gap of a monolayer of g-C3N4.7 was enormously reduced because of the presence of additional densities of states from the doped N atom inside the band gap. These impurity or donor bands are formed inside the band gap region, which ultimately enhance the hydrogen ion reduction reaction enormously.
Keywords: carbon nitride; Density functional theory; hydrogen evolution reaction; nitrogen-rich; Photocatalyst

Unconventional hole doping of S = ½ kagome antiferromagnet CoCu3(OH)6Cl2 - Mandal, Rimpa; Ninawe, Pranay; Ananthram, K. S.; Mhase, Akash; Gupta, Kriti; Saha, Sauvik; Ugale, Ajay; Singh, Kirandeep; Tarafder, Kartick; Ballav, Nirmalya (Advanced Physics Research, 2024)
Geometrically perfect S = ½ kagome lattices with frustrated magnetism are typically electrical insulators. Electron or hole doping is predicted to induce an exotic conducting state including superconductivity. Herein, an unconventional strategy of doping an S = ½ kagome lattice CoCu3(OH)6Cl2 is adopted – a structural analogue of a well-known quantum spin liquid (QSL) candidate herbertsmithite (ZnCu3(OH)6Cl2) – by integrating it with reduced graphene oxide (rGO) via in situ redox chemistry. Such an integration drastically enhances the electrical conductivity, resulting in the transformation of an insulator to a semiconductor, corroborating the respective density of states obtained from the density functional theory calculations. Estimation of the magnetic moments, data on the Hall-effect measurements, Bader charge analysis, and photoemission signals, altogether provide a bold signature of remote hole doping in CoCu3(OH)6Cl2 by rGO. The remote doping provides an alternative to the site doping approach to impart exotic electronic properties in spin liquid candidates, specifically, the generation of topological states like Dirac metal is envisioned.